A colorimetric and fluorescent dual-modal displacement probe based on host-assisted modulation of intramolecular charge transfer and deaggregation. Issue 92 (4th November 2019) - Aryal, Gyan H.; Lu, Kunchao; Chen, Guosong; Hunter, Kenneth W.; Huang, Liming
Abstract : A new colorimetric and fluorescent dual-modal displacement probe based on a supramolecular host–guest complex involving macrocycle encapsulation that modulated intramolecular charge transfer and deaggregation. Abstract : A new colorimetric and fluorescent dual-modal displacement probe was developed based on a supramolecular host–guest complex of cucurbit[8]uril (CB8) and a new functionalized perylene derivative involving macrocycle encapsulation that modulated intramolecular charge transfer and deaggregation.